2022
DOI: 10.3390/bioengineering9080364
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest Operations of Cannabis and Their Effect on Cannabinoid Content: A Review

Abstract: In recent years, cannabis (Cannabis sativa L.) has been legalized by many countries for production, processing, and use considering its tremendous medical and industrial applications. Cannabis contains more than a hundred biomolecules (cannabinoids) which have the potentiality to cure different chronic diseases. After harvesting, cannabis undergoes different postharvest operations including drying, curing, storage, etc. Presently, the cannabis industry relies on different traditional postharvest operations, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 126 publications
0
12
1
Order By: Relevance
“…Samples were stored frozen to reduce heat-induced evaporation and oxidation of the volatile components that are the basis of Cannabis aroma. Benefits of low temperature storage have been demonstrated for moisture content and cannabinoid concentrations and likely apply to terpenes and terpenoids as well ( Das et al, 2022 ; Meija et al, 2022 ). The stimuli were exchanged for fresh samples midway through the study.…”
Section: Methodsmentioning
confidence: 99%
“…Samples were stored frozen to reduce heat-induced evaporation and oxidation of the volatile components that are the basis of Cannabis aroma. Benefits of low temperature storage have been demonstrated for moisture content and cannabinoid concentrations and likely apply to terpenes and terpenoids as well ( Das et al, 2022 ; Meija et al, 2022 ). The stimuli were exchanged for fresh samples midway through the study.…”
Section: Methodsmentioning
confidence: 99%
“…36−38 CP has been investigated for enhancement of the drying efficiency and quality of different foods, medicinal plants, and herbs. 39 The direct mechanism of inactivation of fungi using CP has still not been completely unraveled. A scanning electron microscopy examination of plasma posttreated Cordyceps bassiana spores revealed dried, cracked, and flattened propagules, indicating that CP treatment may cause cell wall leakage and destruction, resulting in reduced cell viability.…”
Section: ■ Available Decontamination Techniquesmentioning
confidence: 99%
“…Biosynthesis of primary cannabinoids in cannabis (adapted from ref ). Abbreviations: CBGA, cannabigerolic acid; CBG, cannabigerol; CBDA, cannabidiolic acid; CBD, cannabidiol; THCA, tetrahydrocannabinolic acid; Δ 9 -THC, tetrahydrocannabinol.…”
Section: Available Decontamination Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant secondary metabolite biosynthesis and antioxidant activity can be disrupted and altered during postharvest storage and drying [ 45 , 46 , 47 ]. Storage studies by Grafström et al (2019) over four years showed that CBD is not prone to oxidative degradation and is stable over time, while decarboxylation of THCA to THC which occurs in stored plant material is increased by the presence of oxygen and higher temperatures [ 48 , 49 ]. Specifically, THC concentrations markedly increase from 1.5% to 2.1%, 12.3% and 12.8% when stored at 50 °C, 100 °C, and 150 °C, respectively, due to THCA decarboxylation [ 45 ].…”
Section: Introductionmentioning
confidence: 99%